The Effect of Comic Media on Science Literacy in Fifth Grade Elementary Science Learning - Sholeha, Nataya Anggun; Mayarni, Mayarni (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This study is motivated by problems found in the learning process because the science media used by educators was still conventional. The purpose of this study is to determine the effect of comic media learning on science literacy of students in fifth grade elementary school. This study used a quantitative approach with an experimental method and a quasi-experimental design because it involved two classes. The research sample consisted of 30 students from the control class and 30 students from the experimental class. Data in this study were collected through observation, document analysis, and trials. The results of the study conducted by the researcher showed that in the N-Gain test, the mean N-Gain value for the experimental class was 0.7883, indicating that the average increase in the measured variables was in the high category according to the established criteria. The data in this study were normally distributed and homogeneous. This was evidenced by the normality test obtained a Sig value on Kolmogorov-Smirnov of 0.200> 0.05. And in the Homogeneity test, a value of 0.636> 0.05 was obtained. This comic learning media was also effective in improving the science literacy of fifth grade students of Elementary School. It can be concluded that the use of comic learning media is effective in improving the science literacy of fifth grade students of elementary school.